XI—Moral and aesthetic virtue - Hills, A (Oxford University Press, 2018)
To what extent does a conception of virtue, similar to moral virtue, play a role in aesthetics? I sketch a conception of moral virtue as an orientation towards moral value and moral reasons, a set of dispositions to respond through action and both cognitive and non-cognitive attitudes. I develop a parallel conception of aesthetic virtue, as an orientation towards aesthetic value and reasons. Aesthetic virtue is fundamentally similar to moral virtue, and there are even analogies between specific virtues such as moral and aesthetic courage. I finish by discussing whether aesthetic virtue supports or conflicts with moral virtue.